Long‐term study of tubeless insulin pump therapy compared to multiple daily injections in youth with type 1 diabetes: Data from the German/Austrian DPV registry. Issue 5 (15th April 2018) - Danne, Thomas; Schwandt, Anke; Biester, Torben; Heidtmann, Bettina; Rami‐Merhar, Birgit; Haberland, Holger; Müther, Silvia; Khodaverdi, Semik; Haak, Thomas; Holl, Reinhard W; ,
Abstract : Objective: To examine glycemic control in youth with type 1 diabetes (T1D) who switched from multiple daily injections (MDI) to a tubeless insulin pump (Omnipod Insulin Management System, Insulet Corporation, Billerica, Massachusetts) compared to patients who continued MDI therapy over a 3‐year time period. Research Design and Methods: This retrospective analysis of the German/Austrian Diabetes Patienten Verlaufsdokumentation registry included data from 263 centers and 2529 patients <20 years ( n  = 660 tubeless insulin pump; n  = 1869 MDI) who initiated treatment on a tubeless insulin pump as of January 1, 2013 and had 1 year of data preswitch from MDI and 3 years of data postswitch to a tubeless pump. Outcomes included the change in glycated hemoglobin (HbA1c), insulin dose, and body mass index (BMI) SD score (SDS). Results: Youth with T1D who switched from MDI therapy to a tubeless insulin pump showed better glycemic control at 1 year compared to patients who continued MDI treatment, adjusted mean ± SE: 7.5% ± 0.03% (58 mmol/mol) vs 7.7% ± 0.02% (61 mmol/mol); P  < .001, with no between‐group difference at 2 and 3 years. Total daily insulin dose was lower ( P  < .001) in the tubeless insulin pump group, 0.80 ± 0.01, 0.81 ± 0.01, and 0.85 ± 0.01 U/kg, vs the MDI group, 0.89 ± 0.01, 0.94 ± 0.01, and 0.97 ± 0.01 U/kg, at 1, 2, and 3 years, respectively (all P  < .001). BMI SDS increased in both groups and was not different over time. Conclusions: Treatment with a tubeless insulin pump in youth with T1D was associated with improvements in glycemic control compared to MDI after 1 year and appears to be an effective alternative to MDI.